Activation of Hydrogen Peroxide by Diphenyl Diselenide for Highly Enantioselective Oxaziridinium Salt Mediated Catalytic Asymmetric Epoxidation - Buckley, Benjamin R.; Elliott, Claire E.; Chan, Yohan; Dreyfus, Nicholas; Bulman Page, Philip C. (Synlett, 2013)
The first reported use of benzeneperseleninic acid as a catalytic mediator for oxaziridinium ion catalysed epoxidation is described, providing reaction rates and ee values (up to 85%) similar to those reported when using oxone as the stoichiometric oxidant. A dual catalytic cycle is proposed, in which diphenyl diselenide is initially converted into the perseleninic acid, which in turn oxidises an iminium ion to the corresponding oxaziridinium species, thus facilitating asymmetric oxygen transfer to an alkene.
Keywords: epoxidation; iminium salt; oxaziridinium; diphenyl diselenide; oxidation